The validation of the Vietnamese comprehensive score for financial toxicity (COST) in people with chronic disease - Minh Huu Le; Tuyen Thi Hong Nguyen; Minh Cuong Nguyen; Yen Nhi Tran; Ngoc Duoc Lan Tran; Van Lanh Nguyen (Pharmacia)
Objectives: This study aimed to explore the psychometric properties of the Vietnamese comprehensive score for financial toxicity (COST) among people with chronic disease. Methods: We conducted a cross-sectional study involving 1,022 people with chronic disease in Can Tho City. Exploratory and confirmatory factor analyses were performed to assess construct validity, while Cronbach’s alpha was used to evaluate the scale’s reliability. Results: Our EFA identified two factors explaining 55.0% of the cumulative variance. CFA indicated that the adjusted two-factor model demonstrated a good fit, with a comparative fit index of 0.96, a Tucker-Lewis index of 0.94, and an RMSEA of 0.062. COST scores were significantly correlated with monthly income (p < 0.001). The COST measure demonstrated good internal consistency, with a Cronbach’s alpha coefficient of 0.82. Conclusions: The COST is a valid and reliable measure for people with chronic disease in Vietnam. This scale can be applied in clinical practice to assess the impact of financial toxicity among people with chronic disease.